Negotiating the secular and the religious in the German Empire : transnational approaches - Habermas, Rebekka, 1959- (New York : Berghahn, 2019)
"With its rapid industrialization, modernization, and gradual democratization, Imperial Germany has typically been understood in secular terms. However, religion and religious actors actually played crucial roles in the history of the Kaiserreich, a fact that becomes particularly evident when viewed through a transnational lens. In this volume, leading scholars of sociology, religious studies, and history study the interplay of secular and religious worldviews beyond the simple interrelation of practices and ideas. By exploring secular perspectives, belief systems, and rituals in a transnational context, they provide new ways of understanding how the borders between Imperial Germany's secular and religious spheres were continually made and remade"--
A secular age? The 'modern world' and the beginnings of the sociology of religion / Wolfgang Knöbl -- The silence on the land: ancient Israel versus modern Palestine in scientific theology / Paul Michael Kurtz -- What means to be 'secular' in the German Kaiserreich? An intervention / Lucian Hölscher -- Secularism in the long nineteenth century between the global and the local / Rebekka Habermas -- Retrieving tradition? The secular-religious ambiguity in nineteenth century German-Jewish anarchism / Carolin Kosuch -- Catholic women as global actors of the religious and the secular / Relinde Meiwes -- Negotiating the fundamentals? German missions and the experience of the contact zone, 1850-1918 / Richard Hölzl and Karolin Wetjen.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on April 23, 2019).
JSTOR
Keywords: Germany -- Religion -- 19th century; Germany -- Religion -- 20th century; Transnationalism; Secularism -- Germany -- History -- 19th century; Secularism -- Germany -- History -- 20th century; Germany -- Social conditions -- 1871-1918.; Allemagne -- Religion -- 19e siècle.; Allemagne -- Religion -- 20e siècle.; Transnationalisme; Allemagne -- Conditions sociales -- 1871-1918.; RELIGION -- Comparative Religion; RELIGION -- Essays; RELIGION -- Reference; HISTORY / Europe / Germany; Religion; Secularism; Social conditions; Transnationalism; Germany; 1800-1999; German Kaiserreich, Religion in Imperial Germany, Imperial German Society, Religion and Society, Germany; History